Pyriform Sinus Fistula in Children: Preferred Imaging Modality and Risk Factors for Diagnostic Delay - Chen, Tong; Ge, Guijie; Chen, Jianglong; Zhao, Xiuhao; Sheng, Qingfeng; Zhu, Linlin; Xu, Weijue; Liu, Jiangbin; Lv, Zhibao (Frontiers in Pediatrics, 2020)
Background: Diagnostic delay of pyriform sinus fistula (PSF) continues to challenge clinicians, and the preferred imaging modality is yet to be verified. The purpose of this study was to investigate the preferred imaging modality for PSF and the possible risk factors for a longer diagnostic delay. Methods: Medical records of patients with surgically confirmed PSF from 2014 to 2018 were retrospectively reviewed. A comparison of the first esophagography timing with true-positive (TP) result and that with false-negative (FN) result was made. Data of computed tomography (CT) performed immediately after esophagography were also collected. In addition, factors related to diagnostic delay were analyzed using multivariate regression models. Results: A total of 147 patients aged 0 to 16 years (median: 5.2 years) were enrolled. The mean time since symptom onset for the first esophagography with TP results was significantly longer than that for the examination with FN results (95.18 ± 79.12 vs. 52.59 ± 42.40 days, P = 0.032). When time since symptom onset was less than 12 weeks, false-negative rate (FNR) of the first esophagography was declining dramatically with a longer time interval. Among 18 cases with FN result of the first esophagography, the fistulous tract was identified in 7 cases using immediate CT. The mean of diagnostic delay was 12.28 months. Rural residency was an independent risk factor for a longer diagnostic delay. Conclusion: Joint examination of esophagography and an immediate CT is the preferred imaging modality for the diagnosis of PSF in children. In addition, rural residency is an independent risk factor for a longer diagnostic delay.